A Simplified Radio-Over-Fiber System for Over 100-km Long-Reach n-QAM Transmission - Run-Kai Shiu; You-Wei Chen; Peng-Chun Peng; Shang-Jen Su; Guan-Ming Shao; Justin Chiu; Jyun-Wei Li; Gee-Kung Chang (IEEE Photonics Journal)
A simplified and cost-effective architecture is proposed and experimentally demonstrated with a millimeter wave (MMW) signal over fiber and free-space wireless transmission. The distributed feedback (DFB) laser is operated in optimized settings after measuring its characteristics and thus the 6 Gbps 64–quadrature amplitude modulation (64-QAM) signal can be successfully transmitted after 20- and 50-km fiber and 1-meter wireless transmission with EVM of 5.98% and 6.87%, respectively. Moreover, the EVM of 10.8% over 100-km long reach is also achieved with the 32-QAM modulation format and data rate of 5 Gbps. The experimental results show that the proposed direct modulation scheme can satisfy applications in metro and rural areas.